Response of soil labile organic carbon fractions and carbon-cycle enzyme activities to vegetation degradation in a wet meadow on the Qinghai–Tibet Plateau - Ma, Weiwei; Li, Guang; Wu, Jianghua; Xu, Guorong; Wu, Jiangqi (Geoderma, 2020)
•Vegetation degradation decrease topsoil labile carbon fractions and enzyme activities.•Moisture is the main abiotic driver of soil carbon and enzyme activities.•Vegetation degradation reduce the carbon sink function in the Tibetan wet meadows. Vegetation degradation resulting from climate change and human activities in wet meadows is an important issue worldwide. This phenomenon is known to influence soil labile organic carbon (LOC) and enzyme activities due to changes in environmental conditions. However, little is known about the response of LOC and enzyme activities to vegetation degradation in high-altitude wet meadows. In this study, we examined the response of LOC and carbon-cycle enzyme activities to different intensities of vegetation degradation (i.e., non-degraded (ND), slightly degraded (SD) moderately degraded (MD), and heavily degraded (HD)) in a Tibetan wet meadow. The contents of soil organic carbon (SOC), dissolved organic carbon (DOC), microbial biomass carbon (MBC) and light fraction organic carbon (LFOC) and the carbon-cycle enzyme activities (i.e., cellulase, amylase and β-glucosidase) were investigated in two growing seasons (2016 and 2017). We found that the content of soil SOC and LOC fractions declined with increasing soil depth in each degraded level except for HD. Vegetation degradation significantly decreased the amount of SOC at depths of 0–10 cm and 10–20 cm, and this decrease was attributed to the relative reduction of carbon source input and higher carbon decomposition. Vegetation degradation also significantly reduced the contents of SWC, DOC, MBC, LFOC, amylase and β-glucosidase in the topsoil layers (0–10 and 10–20 cm). However, the corresponding contents in deeper soil layers had no significant differences. In addition, the SWC, DOC, LFOC and the carbon-cycle enzyme activities were higher in 2016 than in 2017. Significant correlations were obtained between SWC, SOC, LOC fractions and enzyme activities. Soil moisture was found to be the main abiotic driver for variation of soil carbon and enzyme activities. Our results indicate that vegetation degradation in the Tibetan wet meadows decreased the quantity of topsoil labile carbon fractions and enzyme activities and heavily degraded vegetation may lead to a change of profile distribution in soil carbon pool.